2018
DOI: 10.1007/s41030-018-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

Volume Management in Pulmonary Arterial Hypertension Patients: An Expert Pulmonary Hypertension Clinician Perspective

Abstract: Fluid volume management in patients with pulmonary arterial hypertension (PAH) is essential in preventing right ventricular failure. Volume overload may be caused by disease progression, indiscretion of dietary sodium and fluid intake, or medication side effects, and is a frequent complication in patients with PAH. Healthcare professionals (HCPs) who care for patients with PAH have a key role in monitoring, preventing, and managing volume overload. Volume management techniques in patients with PAH include mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
(57 reference statements)
1
25
0
Order By: Relevance
“…Our study also showed an increased risk of readmission in patients with renal failure and fluid and electrolyte disturbances, which is consistent with prior data showing a correlation between the presence of renal failure, hyponatremia, hypervolemia, and PH. [20][21][22][23] In addition, alcohol abuse was associated with a significantly higher odds of readmission in the PPH subgroup. This was independent of hypervolemia, fluid and electrolyte disturbances, and renal disease, 24,25 although it could possibly suggest the presence of portopulmonary hypertension.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study also showed an increased risk of readmission in patients with renal failure and fluid and electrolyte disturbances, which is consistent with prior data showing a correlation between the presence of renal failure, hyponatremia, hypervolemia, and PH. [20][21][22][23] In addition, alcohol abuse was associated with a significantly higher odds of readmission in the PPH subgroup. This was independent of hypervolemia, fluid and electrolyte disturbances, and renal disease, 24,25 although it could possibly suggest the presence of portopulmonary hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…Our study also showed an increased risk of readmission in patients with renal failure and fluid and electrolyte disturbances, which is consistent with prior data showing a correlation between the presence of renal failure, hyponatremia, hypervolemia, and PH. 20 23 …”
Section: Discussionmentioning
confidence: 99%
“…Diuretics are the main medication and effectively reduce right ventricular wall stress; however, diuretic-refractory cases require RRT. 6 Sztrymf et al reported that RRT is feasible for AKI complicated with RHF in PAH patients, although it is associated with a poor prognosis. Moreover, the introduction of RRT in unstable PAH patients may be hazardous due to complications such as hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pharmacological treatment, diuretics are used in secondary pulmonary hypertension to reduce afterload 17 . This is supported by their use to lower pulmonary arterial pressure in patients with right heart failure 18 .…”
Section: Discussionmentioning
confidence: 99%